Interhospital transfer delays emergency abdominal surgery and prolongs stay. Issue 11 (1st November 2016) - Limmer, Alexandra M.; Edye, Michael B.
Abstract : Background: Interhospital transfer of patients requiring emergency surgery is common practice. It has the potential to delay surgical intervention, increase rate of complications and thus length of hospital stay. Methods: A retrospective cohort study was conducted of adult patients who underwent emergency surgery for abdominal pain at a large metropolitan hospital in New South Wales (Hospital A) in 2013. The impact of interhospital transfer on time to surgical intervention, post‐operative length of stay and overall length of stay was assessed. Results: Of the 910 adult patients who underwent emergency surgery for abdominal pain at Hospital A in 2013, 31.9% ( n = 290) were transferred by road ambulance from a local district hospital (Hospital B). The leading surgical procedures performed were appendicectomy ( n = 299, 32.9%), cholecystectomy ( n = 174, 19.1%), gastrointestinal endoscopy ( n = 95, 10.4%), cystoscopy ( n = 86, 9.5%), hernia repair ( n = 45, 4.9%), salpingectomy ( n = 19, 2.1%) and oversewing of perforated peptic ulcer ( n = 13, 1.4%). Overall, interhospital transfer ( n = 290, 31.9%) was associated with increases in mean time to surgical intervention (14.2 h, P < 0.001), post‐operative length of stay (1.1 days, P = 0.001) and overall length of stay (1.6 days, P < 0.001). Delayed surgical intervention was observed across all procedure types except surgery for perforated peptic ulcer, where transferred patients underwent surgery within a comparable timeframe to direct admissions. Conclusion: Interhospital transfer delays surgical intervention and increases length of hospital stay. This mandates attention due to the implications for patient outcomes and added burden to the healthcare system. The system did, however, show capability to appropriately expedite surgery for acutely life‐threatening cases.